How Does COVID-19 Affect the Neurobiology of Suicide? - Conejero, I. (Curr Psychiatry Rep, 2021)
PURPOSE OF REVIEW: The aim of this review was to analyze COVID-19 effect on the biological features of suicidal vulnerability and its interaction with suicide-related biological pathways. We carried out a narrative review of international publications on the interactions of COVID-19 with the biological bases of suicide. RECENT FINDINGS: We hypothesize that SARS-CoV-2 interacts with multiple biological processes that underlie suicidal behavior, such as the renin-angiotensin system, nicotinic receptors, and central and systemic inflammation. Social distancing measures may also worsen subjective or objective social disconnection, thus increasing the risk of suicide. Interestingly, the drugs used to prevent suicide could be promising options to counteract brain damage caused by this coronavirus. SUMMARY: SARS-CoV-2 interacts with multiple biological pathways involved in suicide and opens a new window for understanding the suicidal process. The development of suicide prevention treatments in the context of a pandemic may benefit from knowledge on these interactions.